Gender and risk‐taking behaviors influence the clinical presentation of oral squamous cell carcinoma - Susanne Wolfer; Annika Kunzler; Tatjana Foos; Cornelia Ernst; Andreas Leha; Stefan Schultze‐Mosgau (Wiley, 2022)
Abstract Objective The common risk factors for oral squamous cell carcinoma (OSCC) are smoking and alcohol abuse. A small percentage of patients, mostly women, are demonstrating oral cancer without the common risk behavior. This study investigates how gender and different patterns of lifestyle factors influence the clinical presentation of OSCC. Patients and Methods From this retrospective study, demographical and tumor‐specific data and lifestyle factors were analyzed. Statistical analyses were performed using the χ2 test or Fisher's exact test for categorical analysis and the t test, ANOVA test, or Kruskal-Wallis test for continuous variables. The influence of the respective lifestyle factors together with their interactions with the gender on tumor characteristics has been tested using logistic and ordinal cumulative link regression models. Results Among a total of 308 patients, men represented the majority of smokers (87.2%) and the female cohort were largely non‐smokers and non‐drinkers (64.9%). For age, tumor site and N‐stage it looks like that differences of men and women are driven by the different risk behavior. But if the lifestyle factors are taken into account, we observe contrary effects between men and women for T‐, N‐, and UICC‐stage. For different cancer locations we saw opposite effects with gender and risk profile. These effects are not dose‐dependent explainable for gender. Conclusion Some but not all differences in the development of OSCC for men and women are explainable by the respective difference in lifestyle behavior. Some further investigations are necessary to find explanations for the obvious differences between men and women in developing OSCC.